Programming SnO2 gas Sensor using Arduino microcontroller - Almaroof, Hasan Mudar (2018)
Most of the gases are dangerous or bad for human being and environment. Proper attention should be taken while using or transporting these gases. In the present work, these gases will be detected according to the acceptable limits. The Arduino microcontroller attached to a personal computer will be used to detect several gases such as hydrogen, butane, humidity, etc. The sensitive gas is tin dioxide (SnO2) that is fabricated as a unit called MQ-2, MQ-3, and MQ-135 …etc, or other sensors. As the sensors are exposed to a particular gas, a signal is transmitted to the Arduino microcontroller and attached to the personal computer. This signal is processed and calibrated using C language programming to indicate the concentration of the gas. These sensors are necessary for safety and environmental monitoring of the gases mentioned above such as monitoring butane transportation and household usages. The monitored gas data can be shared with other Internet sites or the cloud that can act as a response to the values of gas concentration by giving sounds or turn lights on or other alarm responses. The alarm sounds, and a fan simultaneously can be operated to remove the excess gas and to reduce its concentration to the acceptable levels. The Arduino microcontroller can be operated without the need of a computer after loading the required program. The operation of the Arduino without a computer greatly reduces the cost of installation of a gas sensor. Transmitting of sensor data can be performed by using programs such as Teamviewer if the microcontroller is attached to a computer. Transmitting data can also be performed without a computer by using ESP8266 that can communicate directly to the Internet. The sensor calibration can be done using a linear fitting or exponential fitting. The use of the exponentials fitting is the ultimate accurate method because of the natural shape behavior of the gas sensing curves.